(3QSGdI aj GdYdes - (3HOjY GdReGf GdgePGfj , CMeO Hf GdMSjf Hf jMji GdgePGfj, CHh GdaVd,J (B398 (3g` s
(3ChdgG (B:s
(3GdYde CWGd Gddg HbGc TF HYjO GdeQGe hdG jUWGO HGdSgGe hdG jbSe HGdGRdGe hdG jVHW HGddLGe s
(3BNQgG (B:s
(3hTZd NdhJg HGdZfGA hEYeGQg Ydi GdLeY hdjdJg Ydi GdLeGY hGaQZ LOg Ydi GdcjS hfRd Ydi GdcCS gjgGJ Ke gjgGJ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdMGOjI YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B209s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdCOHs